2016
DOI: 10.1038/srep23430
|View full text |Cite
|
Sign up to set email alerts
|

Treatment temperature and insult severity influence the neuroprotective effects of therapeutic hypothermia

Abstract: Therapeutic hypothermia (HT) is standard care for moderate and severe neonatal hypoxic-ischaemic encephalopathy (HIE), the leading cause of permanent brain injury in term newborns. However, the optimal temperature for HT is still unknown, and few preclinical studies have compared multiple HT treatment temperatures. Additionally, HT may not benefit infants with severe encephalopathy. In a neonatal rat model of unilateral hypoxia-ischaemia (HI), the effect of five different HT temperatures was investigated after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
93
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 76 publications
8
93
2
1
Order By: Relevance
“…In our experience HT has not been neuroprotective after mild brain injury, defined in the Vannucci model as a median area loss below 25% [51,52] . A moderate degree of injury (30-60% tissue loss) is required to see a neuroprotective effect of HT in this model [31,53] . Whether mild injury should be eligible for cooling in neonates is still debated, as the neuroprotective effect of HT has not been clarified for these patients [54] .…”
Section: Discussionmentioning
confidence: 99%
“…In our experience HT has not been neuroprotective after mild brain injury, defined in the Vannucci model as a median area loss below 25% [51,52] . A moderate degree of injury (30-60% tissue loss) is required to see a neuroprotective effect of HT in this model [31,53] . Whether mild injury should be eligible for cooling in neonates is still debated, as the neuroprotective effect of HT has not been clarified for these patients [54] .…”
Section: Discussionmentioning
confidence: 99%
“…However, although most of the studies measured environmental temperature during the insult, few monitored or reported temperature after HI. This is an important consideration since even normal, healthy neonatal rodents often show lower body temperatures in the typical laboratory nesting conditions between P7 and P14 [20] . Core temperature in neonatal rodents will be affected by the amount and composition of nesting material, position in the nest, huddling, distance from the dam, and the time since the last period of suckling.…”
Section: Discussionmentioning
confidence: 99%
“…We had traditionally seen a 25–50% degree of neuroprotection in moderate brain injury [5, 27]. In the mildest injuries, the method of hemispheric area loss is unable to identify small changes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, upon adjusting the model to examine severe injury, the intrahypoxic temperature has been elevated by 1°C. Previously published data on the lack of HT neuroprotection in severe brain injury in the Vannucci model (after 60 and 66% area loss, respectively) [4, 5] comes from an experimental design where the hypoxic insult was administered at an elevated temperature of 37°C rather than the standard 36°C. In addition, a longer hypoxia time was used (150 vs. 90 min).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation